Mindfulness and cognitive task performance in high school students at Sariputra Jambi - Edi Kristianta Ginting; Hendri Ardianto; Komang Sutawan (International Journal of Science and Applied Science: Conference Series, 2025)
The purpose of this study was to explore and determine the extent of mindfulness's influence on cognitive task performance among students at Sariputra High School in Jambi. As well as what problems often occur among students, there are students who are unable to remember the learning material that has been explained by the teacher during class so that students are able to remember the information that has been explained by the teacher to the students. There are also students who lack concentration when carrying out the learning explained by the teacher during class. There are students who are unable to evaluate all the learning information that has been explained by the teacher to the students. There are students who are unable to analyse information and find the most appropriate solutions. This study used a quantitative approach that is highly relevant to the population data survey method. In this study, there were 88 students, obtained using the proportional random sampling technique. This research was conducted at Sariputra High School in Jambi with respondents from grades X-XII in the 2024/2025 academic year. The technique used was data analysis. The results of this study indicate that there is a very positive and significant effect between mindfulness and cognitive task performance with a t-value of 4.451 and a significance value (p) of 0.000 < 0.05. From the results of the simple regression analysis, an R Square value of 0.187 was obtained. This means that mindfulness has an effect on interpersonal communication of 18.7%, with the remaining 81.3% being influenced by other factors. It is known that the more mindfulness is practised by students, the more it will greatly increase their learning potential and concentration and greatly improve their cognitive task performance.